Generational Shadows: Parties of Memory and Hope in El Salvador - Ellen Moodie (Confluenze)
This essay contemplates generation and memory in the recent history of El Salvador. At its core are stories shared by a rising generation of young, middle-class activists with little or no direct memory of the 1980-1992 civil war — and their parents, who lived the war and celebrated the 1992 peace agreements. I contend that the way different generational memories took form, and the form their stories took, emerged from the liberal orientations that permeated the political trajectories of the activists and their parents. However, their stories diverged according to generation: the young activists felt the chill of the “generational shadows” of those who fought, or at least lived, the war.